A terceira onda : história, educação e fascismo na Cubberley Senior High School(1967) - Barbosa, Caroline de Alencar (2019)
The present study developed on the History of Education line from the Post Graduation Program of the Universidade Federal de Sergipe (Federal University of Sergipe) has as central question what has made possible the pratise of fascism inside th e school institution starting from the case of The Third Wave . The study will use priviledged source as the student magazine The Catamount understanding the student newspaper as formative element, as well as a tool that demonstrates the educational livingn ess with the student body point of view. The Third Wave consisted in an experiment realized with students from the second, third and sixth semesters of the Contemporary World History course, taught by professor Ron Jones (1941 --) in the Cubberley Senior Hig h Scholl , located in Palo Alto, California, in the year of 1967. Jones intended to show the students the persuasion capability of a grand leader on educating crowds to discipline, follow ups of an ideology and the obbeyment using as reference the nazi part y which, led by Adolf Hitler, could mobilize the population during the governement years of the Third Reich (1933 1945), in the Second World War (1939 1945) context. I n this research is of supreme importance knowledges around the themes of fascism, Sec ond World War, nazism and Education. We concluded that the fascism is present in our society, calling only for fertile ground and people willing to accept it. Therefore, education is comprehended as vital space for dialogue and enlightment of the student b ody around themes like fascism, its reflexes in our society and its consequences, moreover the reinforcement of the debate around the intolerance inside and outside the school environment.